Effectiveness evaluation of spn-structure of symmetrick block cipher - Кайдалов, Дмитрий Сергеевич; Олейников, Роман Васильевич (Eastern-European Journal of Enterprise Technologies, 2014)
SPN-structure, along with a Feistel network and a Lai-Massey scheme is one of the most common high-level constructs for building symmetric block ciphers. At the same time, not so many papers are devoted to the evaluation of its effectiveness, so research in this area are extremely important. The evaluation method, based on the possibility of distinguishing the SPN-structure from a random permutation is considered in the paper. This method was successfully applied to the Feistel network and the Lai-Massey scheme, so it was expedient to apply it to the SPN-structure as well. To solve this problem, the authors have put forward and proved a theorem on the maximum likelihood of distinguishing the SPN-structure from a random permutation. Algorithm-distinguisher that allows to make a distinction with a certain probability was developed for the 2-round structure. Also, it was proved that it is impossible to make a distinction for 3 or more rounds of the SPN-structure. The results can be used to compare the effectiveness of the SPN-structure with other high-level constructs of symmetric block ciphers